2008
DOI: 10.1111/j.1472-765x.2001.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable α-amylase production by an extreme thermophile Bacillus thermooleovorans

Abstract: S. NARANG AND T. SATYANARAYANA. 2001. Aims:α‐Amylase production by a newly isolated thermophile, Bacillus thermooleovorans, was studied under different cultivation conditions. Methods and Results: The influence of various carbon and nitrogen sources on α‐amylase production was quantified in batch fermentation in shake flasks. Starch and tryptone were observed to be the ideal carbon and nitrogen sources, respectively. Cultivation of the organism in a chemically defined medium consisting of glucose, riboflavin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…The effect of glycine, tryptophan, peptone, tryptone, lysine and yeast extract supplementation of the production medium on enzyme production was studied. Starch and tryptone have been reported to be the ideal carbon and nitrogen sources, respectively [17] . The amylase synthesis by several microorganisms has been correlated to the presence or absence of different nitrogen sources and various amino acids in the growth medium.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of glycine, tryptophan, peptone, tryptone, lysine and yeast extract supplementation of the production medium on enzyme production was studied. Starch and tryptone have been reported to be the ideal carbon and nitrogen sources, respectively [17] . The amylase synthesis by several microorganisms has been correlated to the presence or absence of different nitrogen sources and various amino acids in the growth medium.…”
Section: Resultsmentioning
confidence: 99%
“…The utilization of soluble starch for the production of reasonable amount of extracellular amylase was previously reported by Tiwari et al (2014) and Khusro and Aarti (2015). In contrary to this, Narang and Satyanarayana (2001), and Vijayaraghavan et al (2015) demonstrated the increased amylase yield in the presence of lactose and fructose, respectively, from respective bacterial sources. In the present investigation, among eight nitrogen sources tested, yeast extract (organic nitrogen source) depicted the maximum yield of extracellular amylase.…”
Section: Discussionmentioning
confidence: 40%
“…IMD 435 21. Narang and Satyanarayana (2001) reported 2% starter culture for maximum α‐amylase production from Bacillus thermooleovorans 24. In a shake flask culture KCC103 required adequate agitation as it is aerobic but at high shaking speed above 200 rpm growth and α‐amylase production were reduced, which may be due to shear stress.…”
Section: Discussionmentioning
confidence: 99%